Pyraflufen Tank Mixtures for Efficacy in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to compare Vida (pyraflufen) tank mixtures for glyphosate- resistant kochia control in fallow. Early-season kochia control was best with tank mixtures that included Sharpen (saflufenacil), but tank mixtures including dicamba provided the best control later in the season. No herbicide controlled kochia more than 80% late in the season. All herbicides controlled downy brome more than 90% within 14 days after treatment, and 100% by 21 days after application.
Keywords: Herbicide-resistance; fallow; kochia; downy brome